125k views
5 votes
Solve the system by subsitutuon || x - 3y = -18
5x - 3y = 6

User Eolsson
by
5.7k points

2 Answers

3 votes

Answer:

y=6.4

x=5.04

Explanation:

x=3y-18

5(3y-18)=6

15y-90=6

15y=96

y=6.4

5x-3(6.4)=6

5x-19.2=6

5x=25.2

x=5.04

User Semen Shekhovtsov
by
4.2k points
6 votes
X=3y-18
Sub that X=3y-18 into equation 2
5(3y-18) -3y =6
15y - 90 - 3y = 6
15y - 3y = 6 + 90
12y = 96
12y/12 = 96/12
Y = 8

Then sub y=8 in the first equation
x - 3(8) = -18
x - 24 = -18
x = -18 + 24
x = 6

Therefore the solution is (6,8)
User Kylex
by
5.2k points